1995
DOI: 10.1111/j.1600-0897.1995.tb00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Uterine Cervix: Characterization of Isolated Lymphocyte Phenotypes and Immunoglobulin Secretion

Abstract: These studies represent the first analysis of viable mononuclear cells isolated from normal cervical tissue. The results form a baseline from which it will now be possible to compare changes that occur at the cervical squamocolumnar junction in response to infection or neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…Immunohistochemical examinations of tissue sections or dispersed cells have indicated that the human endocervix contains larger numbers of immunoglobulin-secreting cells than do the ectocervix, fallopian tubes, and vagina (3,18). Almost all IgA-producing cells contain joining chains and the secretory component (SC), a marker of synthesis of polymeric IgA.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical examinations of tissue sections or dispersed cells have indicated that the human endocervix contains larger numbers of immunoglobulin-secreting cells than do the ectocervix, fallopian tubes, and vagina (3,18). Almost all IgA-producing cells contain joining chains and the secretory component (SC), a marker of synthesis of polymeric IgA.…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of HPV infections in individuals with cell-mediated immunodeficiencies (24) clearly demonstrates the pivotal role of CMI in the resolution of HPV infections. Cervical tissue contains a full complement of immune cells including antigen-presenting cells (APCs), and intraepithelial and submucosal lymphocytes (25,26). There is compelling evidence to suggest that these cells participate in the local immune response to HPV (9,27).…”
Section: Cell-mediated Immune (Cmi) Responsesmentioning
confidence: 99%
“…Less information is available for the male system, but IgA-secreting plasma cells and pIgR-expressing epithelial cells occur in the urethral glands of Littré, epididymis, prostate, and seminal vesicles of humans (1,37,39) and mice (36). The secretions of both male and female systems contain significant levels of SIgA, but these may be exceeded by IgG levels, at least in humans and other primates (3,4,6,9,18,26,27). Whereas SIgA is accepted as the distinct product of the CMIS, the source and means of delivery of IgG are less clear: both local production and transudation from the circulation have been implicated (reviewed in references 2 and 23).…”
mentioning
confidence: 99%